The cenozoic marine tephra record in Indian Ocean deep drill sites - Kutterolf, Steffen; Schindlbeck, Julie Christin; Pank, Katharina; Schmitt, Axel Karl; Lee, H.-Y.; Wang, Kuo-Lung (Journal of volcanology and geothermal research, 2023)
Provenance studies of widely distributed tephra deposits are important to deduce systematic changes in the source, size, distribution, and temporal variation of regional explosive volcanism. Long-term deep ocean drilling sedimentary records are particularly useful for these kind of studies. In this study, we establish a robust tephrochronostratigraphy for 235 primary marine tephra layers collected during International Ocean Discovery Program Expeditions 353, 354, and 362, complemented by older drill cores from Deep Sea Drilling Program and Ocean Drilling Program Legs 22, 119, 120, 121, and 183. We infer at least two major phases of highly explosive arc volcanism during the Early Miocene to Pleistocene, as well as three episodes related to explosive ocean island volcanism located in the Kerguelen plateau, the Broken Ridge, and close to Réunion reaching back to the Paleogene. Twenty-two widespread arc-derived tephra layers from individual eruptions can be correlated by geochemical fingerprinting between multiple holes. These provide nine Quaternary and 13 Neogene temporal tie points in the sedimentary sequence including four new UPb zircon ages. Provenance analysis of the marine tephra layers, which is based on glass composition, assign eleven of these layers to a Toba-like source, ranging from 24 Ma to 75 ka, with the youngest correlative being Young Toba Tuff. Based on distribution pattern, thickness decay, and compositional evidence another eleven tephra layers can be assigned to a northern Sumatran Arc or to an Andaman Arc provenance. First-order minimum eruptive volume estimates for the Neogene tephra layers imply eruptive magnitudes ranging from M = 6.5 to M = 7.5, proving a continuous history of large explosive eruptions from the Sumatran/Andaman Arc since the Neogene, as previously known from the Quaternary. - Plain language summary - Knowing the origin of large volcanic eruptions is important to deduce systematic changes in the source, size, distribution, and changes of regional explosive volcanism. In this study we use widely dispersed marine volcanic deposits in the Indian Ocean, so-called marine tephra layers, to reconstruct the history of a) Sumatran highly explosive eruptions over the last 24 Ma, and b) ocean island volcanism frequently observed in the Indian Ocean. The marine deposits are often the only evidence of major eruptions in the past because respective volcanic edifices and terrestrial deposits are often destroyed by subsequent eruptions, eroded or overlain by younger deposits. Deep ocean drilling provides the unique possibility to overcome these problems by recovering long, tephra-bearing marine sediment sequences in the drill cores. We present the results for 235 primary marine tephra layers that have been collected during eight deep drilling campaigns in the Indian Ocean. Twenty-two widespread connections of arc-derived tephra layers are established by comparing distinctive geochemical fingerprints of the tephras between multiple locations. These provide nine Quaternary and 13 Neogene temporal tie points in the sedimentary sequence. The origin of these marine tephra layers is determined based on the unique glass compositions of individual volcanoes and eruptions, assigning 11 of these layers to a Toba-Caldera-like source ranging from 24 Ma to 75 ka, with the youngest correlative being the iconic Young Toba Tuff. Another eleven tephra layers can be assigned to a northern Sumatran Arc or to an Andaman Arc provenance. Our record demonstrates a continuous history of large explosive eruptions from the Sumatran/Andaman Arc since the Neogene. We additionally infer (1) at least two major phases of highly explosive arc volcanism from the Sumatra-Andamen volcanic chain during Early Miocene to Pleistocene times, and (2) three episodes related to explosive ocean island volcanism found in the Kerguelen plateau, the Broken Ridge, and close to Réunion.